Keane [videorecording (DVD)] - Kerrigan, Lodge; Lewis, Damian, 1971-; Breslin, Abigail, 1996-; Ryan, Amy; Holmes, Tina, 1973-; Welch, Christopher Evan; Blake, Larry, 1955-; George, Catherine (Costume designer); Foster, John R., (Photographer) (2004)
William Keane is searching for his 6-year-old daughter who has been missing for months. One day, he meets a young woman and her 7-year old daughter. As he becomes increasingly attached to the child, it emerges that Keane's daughter may never have existed at all.